2010
DOI: 10.1111/j.1758-2229.2009.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio harveyi as a causative agent of the White Syndrome in tropical stony corals

Abstract: We investigated bacterial assemblages associated with corals displaying symptoms of the 'White Syndrome' (WS), a general term used for indicating the appearance of bands, spots or patches of tissue loss, which is devastating wide areas of tropical ecosystems worldwide. We collected WS-diseased (n = 15) and healthy (n = 15) corals from the natural reef (Indonesia, Indian Ocean) and from four large public aquaria. By using culture-dependent and culture-independent techniques, we found that a large fraction (73%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 34 publications
6
76
2
Order By: Relevance
“…Vibrio bacteria have been associated with white band disease (40)(41)(42) and have been shown to cause WS-like disease signs in aquarium-based infection experiments (20,(22)(23)(24). In the current study, however, we found no significant difference in the relative abundance of sequences affiliated with Vibrio bacteria between health states.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Vibrio bacteria have been associated with white band disease (40)(41)(42) and have been shown to cause WS-like disease signs in aquarium-based infection experiments (20,(22)(23)(24). In the current study, however, we found no significant difference in the relative abundance of sequences affiliated with Vibrio bacteria between health states.…”
Section: Discussioncontrasting
confidence: 55%
“…Tissue loss associated with Indo-Pacific WSs has been attributed to a number of etiological agents, including Vibrio bacteria (20)(21)(22)(23)(24), apoptosis (25), ciliates (11,26), helminths (11), viruses (27), and intraspecific chimeric parasites (11,28), suggesting that distinct and potentially distinguishable forms of WSs exist. Based on logical deduction, we contend that the WS lesions observed in this study are not the result of apoptosis or infection by Vibrio bacteria, ciliates, fungi, cyanobacteria, or helminths, because of the low levels and inconsistent presence of these organisms at WS lesion fronts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenic role of V. harveyi in aquarium corals was convincingly demonstrated (Luna et al, 2007(Luna et al, , 2010; it is the main causative agent of RTN and most likely is involved in other white syndromes as well. Fungi are the main suspects with regard to causation of BJS.…”
Section: Agents Causing Diseases and Syndromesmentioning
confidence: 99%
“…strain CO41 (family Shewanellaceae); and in the class Alphaproteobacteria: Paracoccus denitrificans strain JB11 (family Rhodobacteraceae) and Pseudovibrio denitrificans strain JB12 (100% identity, family Rhodobacteraceae). Also, in the class Gammaproteobacteria, isolates of Vibrio coralliilyticus (P1 wild-type strain LMG 23696) and V. harveyi (strain DSM 19623), which have previously been linked to coral disease or are thought to be opportunistic (V. coralliilyticus [82][83][84] and V. harveyi [85,86]), were used as examples of potential pathogens.…”
Section: Methodsmentioning
confidence: 99%